2020
DOI: 10.1097/mou.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in renal stone formers: are we improving?

Abstract: Purpose of review Health-related quality of life (HRQOL) is a multidimensional construct measuring how disease impacts one's life. In the context of nephrolithiasis this is particularly relevant given the active and quiescent phases of the disease which may not correlate with the traditional index of stone free status. Several instruments are now available to objectively measure HRQOL in this population, including the first disease-specific instrument. Therefore, an overview of emerging data on HRQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The first report on gender differences in HRQoL utilized SF-36, a nonspecific PROM, and found greater impairment in HRQoL for women compared to men on all domains, although a statistically significant difference was only identified for vitality in the multivariable analysis [26]. This is consistent with later studies, which have also reported a lower HRQoL among women when compared to men [18,[27][28][29]. Using a disease-specific questionnaire, Stern et al showed a reduction in [17].…”
Section: Demographics and Socioeconomical Statussupporting
confidence: 56%
See 1 more Smart Citation
“…The first report on gender differences in HRQoL utilized SF-36, a nonspecific PROM, and found greater impairment in HRQoL for women compared to men on all domains, although a statistically significant difference was only identified for vitality in the multivariable analysis [26]. This is consistent with later studies, which have also reported a lower HRQoL among women when compared to men [18,[27][28][29]. Using a disease-specific questionnaire, Stern et al showed a reduction in [17].…”
Section: Demographics and Socioeconomical Statussupporting
confidence: 56%
“…Changes of HRQoL from baseline are not therefore measured [15]. The Wisconsin Stone QoL Questionnaire (WISQoL) is the most used KSD-specific PROM in current clinical research [16][17][18][19]. Its validity has been well established [19][20][21].…”
Section: Key Pointsmentioning
confidence: 99%
“…The total score was 100, and the higher the score, the better the life ability. Anxiety (SAS) Rating [ 9 ]. Evaluation of patient anxiety, a total of 20 projects, 50 are divided into standard points, patient anxiety degree is negatively correlated with the standard points.…”
Section: Methodsmentioning
confidence: 99%
“…Patient experiences and patient reported outcome measures have been increasingly recognized as important factors in treatment decisions [6][7][8]. Emerging data show the utility of validated quantitative instruments in demonstrating changes in health-reported quality of life (QoL) before and after treatment [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%